Experimentation in wicked situations: how activists construct pragmatic action frames - Savaget, P; Roulet, T; Ventresca, M (SAGE Publications, 2024)
Experimentation is key in wicked situations; it provides small wins while keeping several options open for the future. The literature is however scarce on how experimentation is framed, a crucial aspect to the understanding of how actors identify and pursue experiments in situations that are constantly changing and lack a clear resolution. We address this gap by drawing on the concept of ‘action frames’ and deploying a comparative case study of nine cases in diverse contexts in which activists experimented with wicked problems. We find that activists pragmatically shy away from pursuing a permanent solution to focus instead on achieving small wins, diagnosing ‘symptoms’ rather than ‘root causes’ of problems, and ‘working around’ institutional constraints instead of directly ‘confronting’ them. This pragmatic action frame prompts them to initiate pilot experiments that involve trial-and-error and collective learning, and that sometimes scaffold into cumulative small wins. Reflecting on our findings, we build a model of how pragmatic action frames fuel distributed possibilities to experiment in wicked situations. Our model contributes to the literature on wicked problems by revealing how activists ‘welcome’ complexity instead of ‘taming’ it. We contribute to the literature on action frames by demonstrating how multiple viable pragmatic action frames are constructed iteratively without threatening an alternative, dominant frame. Lastly, we contribute to the literature on robust action by demonstrating how pragmatic action frames pave the way for distributed experimentation and by unpacking the core attributes that make ‘robust actors’ accepting of open-ended wayfinding journeys.